Academics at play: Why the "publication game" is more than a metaphor. Issue 4 (September 2020) - Butler, Nick; Spoelstra, Sverre
It is increasingly common to describe academic research as a "publication game, " a metaphor that connotes instrumental strategies for publishing in highly rated journals. However, we suggest that the use of this metaphor is problematic. In particular, the metaphor allows scholars to make a convenient, but ultimately misleading, distinction between figurative game-playing on one hand (i.e. pursuing external career goals through instrumental publishing) and proper research on the other hand (i.e. producing intrinsically meaningful research). In other words, the "publication game" implies that while academic researchers may behave just like players, they are not really playing a game. Drawing on semi-structured interviews, we show that this metaphor prevents us, ironically, from fully grasping the lusory attitude, or play-mentality, that characterizes academic work among critical management researchers. Ultimately, we seek to stimulate reflection about how our choice of metaphor can have performative effects in the university and influence our behavior in unforeseen and potentially undesirable ways.